Work Relationship Terminated Employees Legal Protection To Get Severance Payment From PT. Kertas Lecess Related To Law Of Bankruptcy And Law Of Labor - Susilawati Ussy RafaRayya (Universitas Widya Gama Malang, 2020)
This research titled is work relationship terminated employees legal protection to get severance payment from PT. Kertas Lecess related to law of bankruptcy and law of labor. The position of the worker or labor can be seen in two aspects, namely in terms of juridical and socio-economic aspects. From a socio-economic point of view, workers need legal protection from the state for the possibility of arbitrary action by entrepreneur. The form of protection provided by the government is by making regulations that bind workers and employeee, in this case there is Law Number 37 of 2004 concerning Bankruptcy and Delaying Obligations of Debt Payment Jo. Law Number 13 of 2003 concerning Labor Jo. MK Decision No. 67 / PUU-XI / 2013PT. The regulation is used as a basis for employees of PT. Kertas Lecess to sue the BUMN to be declared bankrupt and responsible for paying severance for its employees. PT. Kertas Lecess is a state-owned enterprise (BUMN), which went bankrupt in September 2019. There are around 1800 workers who must receive termination of employment. The value of severance payment for workers affected by layoffs is around Rp. 300 billion. Employees affected by layoffs protest because they have not received severance payment and even 1,900 employees who have not received their salary for 4 years. PT. Kertas Lecess was decided bankrupt by the Surabaya Commercial Court as a result of the cancellation of the peace proposal submitted by 15 of his employees on September 25, 2018. With the above considerations, the Panel of Judges of the Surabaya District Court, decided to grant the request for a cancellation of peace (Homologation) and stated that PT. Kertas Lecess is proven guilty of negligence for the non-payment of the salaries of PT. Kertas Lecess employees.